Differential utilization of nuclear and extranuclear receptor signaling pathways in the actions of estrogens, SERMs, and a tissue-selective estrogen complex (TSEC). Issue 158 (April 2016) - Madak-Erdogan, Zeynep; Gong, Ping; Katzenellenbogen, Benita S.
Highlights: The balance of nuclear ERα vs. ERK2-mediated activities differs for CE vs. E2. CE shows lower recruitment of ERK2 to chromatin than does E2. In TSEC, BZA antagonized CE stimulation of gene expression and cell proliferation. Estrogens plus SERMs modulate chromatin binding, gene expression and proliferation. Combined SERM and CE in the TSEC achieve unique modes of regulation and efficacy. Abstract: Estrogens act through nuclear and extranuclear initiated pathways involving estrogen receptors (ERs) to regulate gene expression and activate protein kinases. We investigated the involvement of extracellular signal-regulated kinase2 (ERK2) and ERα in the activities of estradiol (E2), conjugated estrogens (CEs), selective estrogen receptor modulators (SERMs), and a Tissue-Selective Estrogen Complex (TSEC), a combination of a SERM and CE that has a blended activity. We found that CE and individual CE components were generally less effective than E2 in ERK2 recruitment to chromatin binding sites of E2-regulated genes. Likewise, CE was much less agonistic than E2 in stimulation of proliferation of ERα-positive breast cancer cells. The SERM bazedoxifene (BZA) fully suppressed proliferation stimulated by E2 or CE and reversed gene stimulation by CE or E2, as did the antiestrogen Faslodex. Thus, the balance of biological activities mediated through nuclear ERα vs. ERK2-mediated activities is different for CE vs. E2, with CE showing lower stimulation of kinase activity. Furthermore, at the BZA to CE concentrations in TSEC, BZA antagonized CE stimulation of gene expression and proliferation programs in ERα-positive breast cancer cells. The studies provide molecular underpinnings of the different ways in which SERMs and estrogens support or antagonize one another in regulating the chromatin binding of ERα and ERK2, and modulating gene and cell activities. They illuminate how the combined actions of two classes of ER ligands (SERM and CE, present in TSEC) can achieve unique modes of regulation and efficacy.